On the effect of room temperature ageing of Ni-rich Ni–Ti alloys. (1st July 2015) - Kustov, S.; Mas, B.; Salas, D.; Cesari, E.; Raufov, S.; Nikolaev, V.; Van Humbeeck, J.
Abstract : We show that the cubic–monoclinic martensitic transformation (B2-B19′) in Ni-rich Ni–Ti alloys is strongly affected by room temperature exposure after quenching from 1270 K, presumably due to the initial stage of precipitation: transformation temperatures strongly decrease, the hysteresis increases and in the Ni50.8 Ti49.2 alloy the transformation gets arrested. The suppression of the B2–B19′ transformation is not preceded by the cubic–trigonal (R-phase) transition, indicating that nm-size precipitates or their nuclei do not serve as nucleation sites for the R-phase.